Composition and Functions of Tools in Banking Supervision in Post-Soviet Republics (Russia and Tajikistan) - M. Kurbonalizoda; F. M. Ismatulloeva (Вестник Российского экономического университета имени Г. В. Плеханова, 2019)
The article studies the most widely used tools of banking supervision, such as macro-economic control, distributive and structural control, finance sanitation. Among regulation tools of central banks a special role is attributed to normative and legal acts, methodological and preventive tools. The authors propose to divide all tools of banking supervision into two big categories: control and supervision (key ones) and tools of regulation (extra ones). One of the most important analytical tools meant to provide estimation of potential losses of credit organizations in case of economic recessions is macro-prudential stress-testing. It was grounded that tools of banking supervision and regulation cannot always allow us to reach a goal set by central banks of post-soviet countries, i.e. to lower the inflation rate. Cut in Inflation rate should not be the main goal of regulators. During the transition period in economy central banks should resolve wider range of tasks and use tools of banking supervision and regulation.